Disaster Resilience into Which Direction(s)? Competing Discursive and Material Practices in Post-Katrina New Orleans. Issue 4 (2nd October 2018) - Paidakaki, Angeliki; Moulaert, Frank
ABSTRACT: Making use of theories of discourse and social innovation, this paper analyses the resilience of post-Katrina housing reconstruction trajectories in New Orleans. It defines and connects the concepts of hegemonic and counter-hegemonic social resilience cells (SRC), institutional structures and housing reconstruction trajectories as the pillars of the housing systems. SRC are the key agents in these systems and have been the main architects of the multidirectional housing recovery trajectory in New Orleans. Their discursive and material practices, and the way they interact with institutional structures are studied for two periods in the post-Katrina recovery process. Based on the main features of their practices and institutional affinities SRC can be divided into three types: hegemonic pro-growth and counter-hegemonic pro-equity and pro-comaterializing SRC. The evidence on the multidirectionality of housing reconstruction trajectories has challenged at least three hegemonic discursive myths about the post-Katrina recovery process: that reconstruction should be planned top-down; without state involvement; and without city-wide political leadership. The paper concludes that socially optimal recovery outcomes can be achieved when institutional structures build alliances with diverse types of SRC and orchestrate resilience trajectories on the basis of equity of treatment.